Authoritarian Parties and Women’s Political Power: A Case Study of Uganda and Tanzania - Gillet, Margaret; Kim, Namkyu (Journal of Global Politics, 2024)
This study investigates the impact of different types of authoritarian regimes on women’s political empowerment, focusing on the comparative analysis of personalist and party-based regimes. Through a paired comparison of Uganda’s personalist regime under Yoweri Museveni and Tanzania’s party-based regime under TANU/CCM, this article examines how each regime responds to both domestic and international pressures for gender equality. We argue that party-based regimes, with their institutional structures and formal linkages to society, are better equipped to make credible policy concessions and genuinely empower women. They use inclusive policies to secure mass support and maintain legitimacy, enhancing their ability to navigate elite cohesion and ensure regime stability. In contrast, personalist regimes, characterized by centralized power and lack of executive constraints, often use women’s representation as a form of superficial compliance to international norms rather than a genuine empowerment effort. We demonstrate that despite similar incentives to co-opt women under international pressure, party-based regimes exhibit a higher capacity for delivering substantive women’s political empowerment due to their institutional strengths and formal societal linkages. KCI Citation Count: 0